2013
DOI: 10.1123/ijsnem.23.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Skeletal-Muscle Glycogenolysis and Perceived Exertion With Progressive Dehydration During Cycling in Hydrated Men

Abstract: This study investigated the effects of progressive mild dehydration during cycling on whole-body substrate oxidation and skeletal-muscle metabolism in recreationally active men. Subjects (N = 9) cycled for 120 min at ~65% peak oxygen uptake (VO2peak 22.7 °C, 32% relative humidity) with water to replace sweat losses (HYD) or without fluid (DEH). Blood samples were taken at rest and every 20 min, and muscle biopsies were taken at rest and at 40, 80, and 120 min of exercise. Subjects lost 0.8%, 1.8%, and 2.7% bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Only 2 players in the CES trial had a peak Tc greater than 39°C, compared with 8 players in NF. The 0.3°C difference in Tc is lower than the 0.5-0.6°C difference measured in studies of 2% dehydration during steady-state exercise in the laboratory (Logan-Sprenger et al 2012, 2013Baker et al 2007), but similar to the 0.4°C difference measured during a self-paced soccer game (Edwards et al 2007). During the same period that Tc was reaching its peak in the present study, players in the CES trial had increased skating speed and time at high effort.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Only 2 players in the CES trial had a peak Tc greater than 39°C, compared with 8 players in NF. The 0.3°C difference in Tc is lower than the 0.5-0.6°C difference measured in studies of 2% dehydration during steady-state exercise in the laboratory (Logan-Sprenger et al 2012, 2013Baker et al 2007), but similar to the 0.4°C difference measured during a self-paced soccer game (Edwards et al 2007). During the same period that Tc was reaching its peak in the present study, players in the CES trial had increased skating speed and time at high effort.…”
Section: Discussionmentioning
confidence: 81%
“…Sweat rates in CES and NF were similar, while Tc was lower in CES, suggesting that there was increased heat transfer from the core of the body to the periphery in CES. Logan-Sprenger et al (2012, 2013 reported lower Tc in both men and women while cycling in a temperate environment while staying hydrated with water versus progressive mild dehydration, even though sweat rates were identical. During exercise, the cardiovascular system must provide adequate blood flow to the contracting muscles to maintain the exercise intensity and to the skin for adequate heat dissipation.…”
Section: Discussionmentioning
confidence: 86%
“…More recently, we reported a 24% increase in total muscle glycogen use over 2 h of cycling at 65% VO 2peak in male subjects dehydrated to 2.7% BM loss, with no difference in plasma [EPI] or the energy status of the muscle, but a greater Tc between trials (Logan-Sprenger et al. 2013a). There appears to be at least three potential mechanisms that may account for the upregulated glycogen phosphorylase (PHOS) activity and subsequent glycogen use with dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…(Logan-Sprenger et al. 2013a, 2013b). However, Tc was significantly greater in DEH subjects with 1–2% BM loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation